Nano-Micro Encapsulation of Drugs - Clares, Beatriz; Calpena, Ana C. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue covers different aspects of the nano/microencapsulation of drugs, including papers describing the design, preparation, and characterization of nano- and micro-carrier-based drug delivery systems and the latest developments in key fields. Eight articles regarding this topic were selected for this Special Issue, demonstrating the potential of this development strategy for drug delivery in a wide range of applications (from cancer treatment to wound healing, as well as cardiovascular or ocular diseases). Prestigious experts in these fields have participated in this Special Issue, sharing their research and contributions with authors affiliated with different Universities and other renowned and well-respected institutions.